Direct current stimulation increases blood flow and permeability of cortical microvasculature in vivo. (17th November 2022) - Gellner, Anne‐Kathrin; Frase, Sibylle; Reis, Janine; Fritsch, Brita
Abstract: Background and purpose: Transcranial direct current stimulation (DCS) structurally and functionally modulates neuronal networks and microglia dynamics. Neurovascular coupling adapts regional cerebral blood flow to neuronal activity and metabolic demands. Methods: In this study, we examined effects of anodal DCS on vessel morphology, blood flow parameters, permeability of cortical microvasculature, and perivascular microglia motility by time‐lapse two‐photon microscopy in anaesthetized mice. Results: Low‐intensity DCS significantly increased vessel diameter and blood flow parameters. These effects were transient and dependent on the spontaneous vasomotion characteristics of the individual vessel. Vessel leakage increased significantly after DCS at 1.1 and was more pronounced at 2.2 A/m 2, indicating a dose‐dependent increase in vascular permeability. Perivascular microglia exhibited increased soma motility post‐DCS at both intensities, potentially triggered by the extravasation of intravascular substrates. Conclusions: Our findings demonstrate that DCS affected only vessels with spontaneous vasomotion. This rapid vascular response may occur as an adaptation of regional blood supply to neuronal excitability altered by DCS or as a direct effect on the vessel wall. In contrast to these immediate effects during stimulation, increases in cortical vessel permeability and perivascular microglia motility appeared after the stimulation had ended. Abstract : Direct current stimulation (DCS) rapidly increased diameter and blood flow parameters in cortical microvasculature as assessed via two‐photon microscopy in anaesthetized mice. This effect was transient and dependent on spontaneous vasomotion characteristics. The rapid vascular response may reflect an adaptation of regional blood supply to neuronal excitability altered by DCS or a direct effect on the vessel wall. DCS also significantly increased vascular permeability in a dose‐dependent manner and, together with enhanced soma motility of perivascular microglia, this effect was restricted to the poststimulation period.